The Oral Bioavailability of 8‐Prenylnaringenin from Hops (Humulus Lupulus L.) in Healthy Women and Men is Significantly Higher than that of its Positional Isomer 6‐Prenylnaringenin in a Randomized Crossover Trial. Issue 7 (1st March 2018) - Calvo‐Castro, Laura A.; Burkard, Markus; Sus, Nadine; Scheubeck, Gabriel; Leischner, Christian; Lauer, Ulrich M.; Bosy‐Westphal, Anja; Hund, Verena; Busch, Christian; Venturelli, Sascha; Frank, Jan
Abstract : Scope: Prenylated chalcones and flavonoids from hop ( Humulus lupulus L.), such as 6‐prenylnaringenin (6‐PN) and 8‐prenylnaringenin (8‐PN), are investigated for their health beneficial and anticancer activities. We, thus, compare the oral bioavailability and safety of 6‐PN and 8‐PN in healthy young women and men, and investigated their effects on peripheral blood mononuclear cells (PBMC). Methods and results: A double‐blind, placebo‐controlled, crossover trial is conducted with 16 healthy volunteers (eight women, eight men) given a single oral dose of 500 mg 6‐PN, 8‐PN, or placebo in random order. Maximum total concentrations of 6‐PN and 8‐PN in plasma ( Cmax ; 543 and 2834 nmol L –1 ) and their respective area under the plasma concentration‐time curve (AUC; 3635 and 15801 nmol L –1 × h) are significantly (5.2‐ and 4.3‐fold) higher for 8‐PN than for 6‐PN ( p ˂ 0.05). PBMC for ex vivo experiments are isolated from blood sampled before and 6 h after intake of 6‐PN, 8‐PN, or placebo. Despite the single‐treatment regime and low blood concentrations, both 6‐PN and 8‐PN increase the survival of PBMC relative to control. Conclusion: 8‐PN is significantly more bioavailable in healthy humans than its isomer 6‐PN. Interestingly, 6‐PN, despite being less bioavailable, is similarly effective as 8‐PN in enhancing PBMC viability. Abstract : The oral bioavailability of 6‐prenylnaringenin (6‐PN) and 8‐prenylnaringenin (8‐PN) from hops ( Humulus lupulus L.) is compared in humans in a single dose (500 mg), double‐blind, randomized, placebo controlled, three‐armed, crossover trial. 8‐PN shows significantly higher bioavailability than 6‐PN, without any toxicity or sex‐related effects. Both compounds increase the survival of PBMC, suggesting promising immune‐modulatory effects.